2014
DOI: 10.1680/bbn.14.00009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sacrificial bonds on the mechanical behaviour of polymer chains

Abstract: A growing focus in modern materials science is the attempt to transfer principles found in nature into new technological concepts with the goal of producing novel materials with tailored mechanical properties. One of these principles used in nature is the concept of sacrificial bonding (i.e. non-covalent cross-links that rupture prior to the protein backbone), which is associated with increased toughness in many biological materials. In the present work, the influence of the number and distribution of sacrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The left graph of figure 5 shows the work to straighten the molecule W. For all systems, W shows a linear dependence on the sticky site density (i.e., the number of cross-links). While W does not considerably change between the random and ordered arrangement (as was already observed in [63]), it is consistently higher for the system containing bis-complexes only compared to the system containing trimers. This is remarkable because the complex energies are the same for the dimer and trimer.…”
Section: Load-displacement Curvessupporting
confidence: 69%
See 1 more Smart Citation
“…The left graph of figure 5 shows the work to straighten the molecule W. For all systems, W shows a linear dependence on the sticky site density (i.e., the number of cross-links). While W does not considerably change between the random and ordered arrangement (as was already observed in [63]), it is consistently higher for the system containing bis-complexes only compared to the system containing trimers. This is remarkable because the complex energies are the same for the dimer and trimer.…”
Section: Load-displacement Curvessupporting
confidence: 69%
“…Previous investigations identified the number and the distribution of sticky sites as a major factor determining the mechanical behavior of a polymer cross-linked with dimers [62][63][64]. Therefore, the influence of the same parameters on the mechanical performance is also investigated in the current study and shown in figure 5.…”
Section: Load-displacement Curvesmentioning
confidence: 93%
“…Previous results showed that the topology and arrangement of RCLs have a strong influence on the mechanical response of single polymer chains. 28,45 In the present paper the focus is put on the influence of the RCLs on the strength of the polymeric Fig. 1 Sketch of the used model.…”
Section: Resultsmentioning
confidence: 99%
“…The model presented here is a generalization of the single chain model described previously. 28,45 Each polymer in the system is described as a covalently linked chain of N hard spheres with diameter R oriented along the Z-axis (in the following R is set to the unit of length). Depending on the situation investigated the entire system is made of one, two or nine single chains.…”
Section: The Modelmentioning
confidence: 99%
“…The topic self-healing concepts is addressed by Nabavi et al 3 by computational studies of a simple model for sacrificial bonding, a prominent mechanism for self-healing used in many natural systems such as in mussel byssus threads, for instance. It is demonstrated that the work to fracture in the bioinspired model systems is mainly determined by the number of sacrificial bonds, while stiffness and strength are rather dependent on their distribution.…”
Section: Paris and Zollfrankmentioning
confidence: 99%